2018
DOI: 10.1016/j.apenergy.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical analysis of microcapsules containing phase change materials for cold storage

Abstract: Microencapsulated phase change material slurries (MEPCMSs) offer a potentially efficient and flexible solution for cryogenic-temperature cold storage. In this paper, the phase change material (PCM) microcapsules prepared to form MEPCMSs for cryogenictemperature cold storage consist of Dowtherm J (DJ) as core material and melamine formaldehyde (MF) as primary shell material. DJ is an aromatic mixture with diethylbenzene as the main component. Composite shell materials are adopted to avoid cracking by adding alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…From the XRD results, it can be seen that the cryogenic treatment resulted in crystal structure changes and a slight increase in the crystallinity (for CMPCM1), which was similar to observations from studies related to cryogenic-treated polymers 36 . However, the peak intensity of CMPCM2 was quite low compared to that of CMPCM1, which could be attributed to its encapsulation properties.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…From the XRD results, it can be seen that the cryogenic treatment resulted in crystal structure changes and a slight increase in the crystallinity (for CMPCM1), which was similar to observations from studies related to cryogenic-treated polymers 36 . However, the peak intensity of CMPCM2 was quite low compared to that of CMPCM1, which could be attributed to its encapsulation properties.…”
Section: Discussionsupporting
confidence: 85%
“…However, research studies on powder-based materials treated with cryogen (cryogenic liquid) are limited. Interestingly, one study demonstrated the thermomechanical behavior of microspheres comprising a PCM for cryogenic-temperature cold storage applications 36 . The results infer that the buckling of the shell and freezing time of the PCM microspheres were vital parameters in determining the heat transfer and charging efficacy of cold storage.…”
Section: Introductionmentioning
confidence: 99%
“…The phase change slurry (PCS) is made up of micro-encapsulated PCM (mPCM) and carrier fluid. The mPCM consists of PCM as core material and polymer as shell material [24] . PCS has high latent heat capacity and high energy density as it combines the properties of PCM with liquid coolant.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, as solid-liquid PCMs, paraffin waxes are prone to leakage during the phase change process. To overcome this defect, many studies have been focused on the development of change phase microcapsules (microPCMs), which have a stable core-shell structure composed of an organic/inorganic shell and a PCM core [23,24,25]. In our previous work, we used microPCMs to prepare a low-temperature protective fabric [26].…”
Section: Introductionmentioning
confidence: 99%